2006
DOI: 10.1097/01.brs.0000218583.43398.e3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Evaluation of Posterior Lumbar Interbody Fusion

Abstract: The results of our study demonstrate that the most reliable radiographic indicator of fusion is the presence of bone bridging through the cages shown on coronal planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…First, it is not straightforward to objectively assess the radiographic fusion status, especially with implants in the grafted sites. Computed tomography and MRI are reportedly more reliable to assess the fusion status [23,37], but we did not use these highcost technologies in this study. Blumenthal and Gill [4] stated the only reliable method to determine fusion rate may be reexploration which is obviously impractical on a routine basis.…”
Section: Discussionmentioning
confidence: 76%
“…First, it is not straightforward to objectively assess the radiographic fusion status, especially with implants in the grafted sites. Computed tomography and MRI are reportedly more reliable to assess the fusion status [23,37], but we did not use these highcost technologies in this study. Blumenthal and Gill [4] stated the only reliable method to determine fusion rate may be reexploration which is obviously impractical on a routine basis.…”
Section: Discussionmentioning
confidence: 76%
“…Although b-TCP used for spinal fusion has been found to be satisfactory in animal models [15], lumbar posterior fusion [5] and anterior cervical fusion [16], no reports on b-TCP as the single filling material for PLIF cages have been found. Several studies have shown that there is good evidence to support the use of b-TCP as a bone graft extender for posterolateral fusion [17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple radiological methods, like dynamic and static radiographs [8-10, 17, 23], magnetic resonance imaging [16] and CT scans [9,26], have been used to assess fusion status. In addition, a wide variety of criteria and classification systems have been published [3,27].…”
Section: Discussionmentioning
confidence: 99%
“…In order to address this question, we aimed to compare the agreement and confidence between independent assessors in determining fusion using both MRI and CT postoperatively following ALIF. Although the role of MRI in evaluating lumbar fusion has been studied previously, 14 to the authors knowledge this is the first study evaluating MRI for fusion in ALIF and also the first study to compare MRI and CT.…”
Section: Introductionmentioning
confidence: 99%